Analisis Disiplin Kerja pada PT. X Gresik - Sri Wulan Eka Dwiyanti; Roziana Ainul Hidayati (SAFE-Network, 2023)
The purpose of this research is useful in identifying causes and solutions to employee discipline applied in daily work activities. This study processes data from respondents and informants who were asked for information or extracted data. The data processed from the research object is an indicator of employee work discipline with a qualitative descriptive method. Collection techniques with interviews, observation and collection of documentation. The data is analyzed against the problems encountered. The research results obtained from all indicators that affect discipline have been carried out well, but leaders need to improve in giving appreciation. Other factors that cause employees to be late for work are overtime activities and work environment or congested road access. The solution that can be done is by carrying out direct supervision or by utilizing technology (systems) that can monitor employee activities from the daily reports that employees work on. Conditions must be created in a comfortable work environment by improving road access, transferring attendance media (fingerprints) near the parking area. Continuous work evaluation is the provision of direction and motivation and the provision of periodic sanctions in order to achieve a higher level of discipline and to have a positive impact on the company.